2015
DOI: 10.1159/000438511
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis-Associated Endothelial Cell Apoptosis by MiR-429-Mediated Down Regulation of Bcl-2

Abstract: Background/Aims: Endothelial cell injury and subsequent apoptosis play a key role in the development and pathogenesis of atherosclerosis, which is hallmarked by dysregulated lipid homeostasis, aberrant immunity and inflammation, and plaque-instability-associated coronary occlusion. Nevertheless, our understanding of the mechanisms underlying endothelial cell apoptosis is still limited. MicroRNA-429 (miR-29) is a known cancer suppressor that promotes cancer cell apoptosis. However, it is unknown whether miR-429… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Among the available models, the apoE -/- mouse was the first and most widely used for this purpose. Loss of apoE gene expression in this animal compromises the hepatic clearance of VLDL and LDL, leading to spontaneous hypercholesterolemia [1, 3, 7]. Moreover, apoE -/- mice exhibit impaired vasodilation and enhanced vasoconstriction responsiveness, which are hallmarks of endothelial dysfunction in this experimental model and in atherosclerotic humans [4, 5, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the available models, the apoE -/- mouse was the first and most widely used for this purpose. Loss of apoE gene expression in this animal compromises the hepatic clearance of VLDL and LDL, leading to spontaneous hypercholesterolemia [1, 3, 7]. Moreover, apoE -/- mice exhibit impaired vasodilation and enhanced vasoconstriction responsiveness, which are hallmarks of endothelial dysfunction in this experimental model and in atherosclerotic humans [4, 5, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have declared that the mechanisms underlying miRNA regulation of endothelial apoptosis are often attributed to targeting critical genes or the pivotal pathways related to apoptosis [36, 37]. Here, we discovered that miR-210 regulated endothelial apoptosis by targeting PDK1.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, a growing body of recent data has shown that circulating miRs could influence the development and progression of vascular diseases, including atherosclerosis [24,25]. Although atherosclerosis is common in clinical practice, the mechanisms of its genesis have …”
Section: Discussionmentioning
confidence: 99%